Shwasa–Prashwasa Prakriya (The process of Respiration) in Ayurveda: A Review - Bhawsar, Priyanka; Nampalliwar, Amit (International Research Journal of Ayurveda & Yoga, 2021)
In Sharangdhara samhita respiratory system dealt in small context in a four-line shloka, this description speaks anatomical as well as physiological aspects. Sharangdhara samhita is written in 14th century and analyzing commentaries written in 16th (Deepika) and 18th (Goodartha Deepika) century AD on respiration in Ayurveda. Pranavayu located at nabhi (umbilicus) by touching the heart comes out through the throat to drink ‘Vishnupadamruta’ or ‘Ambarpiyusha’. After assimilating ‘Vishnupadamruta’ or ‘Ambarpiyusha’, it comes back quickly into the body to nourish the entire body and nourishes ‘Jatharagni (digestive fire)’. Considering physiological aspect of respiration, this concept has been correlated with modern consideration of respiration and discussed in this paper.